The Effect of 17-methoxyl-7-hydroxy-benzene-furanchalcone Isolated from Millettia pulchra on Myocardial Ischemia In Vitro and In Vivo - Jian, Jie; Qing, Feizhang; Zhang, Shijun; Huang, Jianchun; Huang, Renbin (Planta Medica, 2012)
The effect of 17-methoxyl-7-hydroxy-benzene-furanchalcone isolated from the roots of Millettia pulchra (Benth.) Kurz var. Laxior (Dunn) Z. Wei on rat myocardial ischemia has been investigated. An in vitro cardiocyte apoptosis model and an in vivo myocardial ischemia model were used to elucidate the mechanism of 17-methoxyl-7-hydroxy-benzene-furanchalcone. In contrast to hydrogen peroxide (H2O2, 100 µmol/L), 17-methoxyl-7-hydroxy-benzene-furanchalcone in vitro (255 and 510 µmol/L) increased the quantity of total superoxide dismutase and the protein expression of B cell lymphoma/leukemia-2, while it inhibited cardiocyte apoptosis, the release of malondialdehyde and tumor necrosis factor α, and protein expression of nuclear factor κ Bp65 and Bcl-2-associated X protein. Furthermore, pretreatment with MHBFC in vivo (10 and 20 mg/kg) decreased heart rate, systolic pressure, diastolic pressure, average pressure, left ventricular systolic pressure, the largest upstroke velocity of the left ventricular pressure (+ dp/dtmax), total antioxidative capability, myoglobin isoenzyme of creatine kinase, and inducible nitric oxide synthase, while it increased endothelial nitric oxide synthase, ATPases, left ventricular diastolic pressure, left ventricular end-diastolic pressure, the largest descendent velocity of the left ventricular pressure (−dp/dtmax) and the interval from the beginning of left ventricular contraction to +dp/dtmax (t − dp/dtmax), all in a dose-dependent manner. Our present results suggest that 17-methoxyl-7-hydroxy-benzene-furanchalcone is an attractive antimyocardial ischemia agent mostly because of its negative heart rate and negative inotropic effects, the reduction in myocardial oxidative damage, and the modulating expression of genes associated with apoptosis, which improves diastolic function.
Keywords: 17-methoxyl-7-hydroxy-benzene-furanchalcone; Millettia pulchra Papilionaceae; myocardial ischemia; apoptosis; peroxidation; cardiac hemodynamics